Surveying the ALS Population of Columbus and Dayton Over Their Thoughts of the Possible Placement of a Comprehensive ALS Center in Central Ohio - Madison Nicole McClain (The Journal of Undergraduate Research, 2013)
The study focused on surveying the ALS community (patients, family members to patients, and caregivers) on their thoughts about the possible placement of a comprehensive ALS center in central Ohio. The study design created an original survey that was distributed online through the ALS Association Central & Southern Ohio chapter’s monthly newsletter (April) and in-person at two Columbus support group meetings and one Dayton support group meeting. Data from the survey was complied and analyzed in pie charts to determine various trends in the responses. Overall, the ALS community supported the creation of an ALS center and felt it would be beneficial to them. It is recommended that a fiscally responsible, lightly staffed ALS center be created to meet the needs of the ALS patients of central Ohio.